Factors Affecting Bank Profitability of BUKU 1 and BUKU 2 - Lis Sintha Oppusunggu; Lita Dwipasari (University of Merdeka Malang, 2021)
The research aims to know and analyze the effect of bank health ratios in terms of capital aspects (CAR and CCRA), rentabilities aspects (ROA, OEOI, and NIM), and liquidity aspects (LDR and LAR) on Profitability in BUKU 1 and BUKU 2 group banks. This study used secondary data obtained from monthly financial statements on banks category BUKU 1 and BUKU 2 period January 2015-December 2019 while analyzing data using the multiple linear regression analysis approaches. The results found that 1) aspects of bank capital as measured by capital Adequacy Ratio and Core Capital Ratio to ATMR consistently had no significant effect on profitability in the BUKU 1 and BUKU 2 group banks; 2) Aspects of Rentability as measured by ROA and NIM proved to have a negative and significant effect on bank profitability in the BUKU 1 and BUKU 2 groups, While for Operating Expenses or Operating Income proved to have a significant negative effect on bank profitability and 3) Aspects of liquidity as measured by LDR and LAR proved to have a positive and significant effect on profitability in banks in the BUKU 1 and BUKU 2 groups, and 4) Among bank health ratios, it was found that LDR was the dominant variable on the profitability on banks in the BUKU 1 and BUKU 2 groups.JEL: G21, G23, G53